Peranan Hakim Mediator dalam Melakukan Mediasi Terhadap para Pihak yang Akan Bercerai di Pengadilan Agama Cibinong - Salwa Zahrani Rachman; Yono; Syarifah Gustiawati M (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Alternative Dispute Resolution (ADR) is a way to resolve disputes that is humane and fair. Humane because the decision (peace agreement) is the authority of the disputing parties and maintains good relations. Fair because each party negotiates a solution to the problem and the results are satisfactory, based on PERMA (Supreme Court Regulation) no. 1 of 2016 every divorce or dispute problem registered in court must follow the procedure that the parties to the case or the attorney must go through a mediation process first before proceeding to the next trial stage, but in reality the increase in divorce cases continues to increase every year, because public understanding of the law increases and there are many other factors, a mediator makes his position as a neutral party to the decisions of the parties, This study uses a qualitative research method, namely field research with observation, interview and documentation techniques, The purpose of this study is first, To explain the mediation process carried out by the Judge in resolving divorce cases. Second, To explain the Mediator Judge's Strategy in mediating Divorce cases. Third, To find out the role of the Judge in mediating the case resolution process at the Cibinong Religious Court. The results of this study indicate that in its role, the mediator judge ensures that the mediation process runs according to the law, provides understanding, and provides advice based on religion, personal experience, and successful mediation cases. In this case, it is done with the aim that the parties in the case at the Cibinong Religious Court are expected to make whatever the decision in court or the results of the mediation process as a valuable lesson in living together in the future.